1997
DOI: 10.1097/00000478-199702000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Minimal Residual Cancer In Radical Prostatectomy Specimens

Abstract: Residual cancer in radical prostatectomy specimens from men with biopsy-proven adenocarcinoma occasionally may be difficult, or even impossible, to identify. Although this finding was recently described as "minimal residual cancer" or the "vanishing cancer phenomenon," there are no data on the incidence of this phenomenon in surgical pathology practice. We evaluated 3,038 consecutive radical prostatectomies performed at the Johns Hopkins Hospital between 1988 and 1995, excluding cases with a history of transur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 13 publications
0
52
0
7
Order By: Relevance
“…The present incidence of no residual cancer is about two cases per 1000 RPs. This decline may be offset in recent years by two factors: (i) an increase in the number of patients receiving preoperative androgen deprivation therapy (or radiation therapy), which causes an apparent reduction in cancer volume in some patients, although this trend was not apparent in the present data because such therapy was given only rarely; and (ii) increasing vigilance in screening shows that prostate cancer is now being detected at a smaller volume and lower stage than before [1].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The present incidence of no residual cancer is about two cases per 1000 RPs. This decline may be offset in recent years by two factors: (i) an increase in the number of patients receiving preoperative androgen deprivation therapy (or radiation therapy), which causes an apparent reduction in cancer volume in some patients, although this trend was not apparent in the present data because such therapy was given only rarely; and (ii) increasing vigilance in screening shows that prostate cancer is now being detected at a smaller volume and lower stage than before [1].…”
Section: Discussionmentioning
confidence: 56%
“…The incidence of 'vanishing cancer' in RP samples is uncertain, with only one study finding two cases in 3038 consecutive RPs [1]. The clinical significance of this finding is unknown and there are no previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Mazzucchelli et al, 9 in a study of 1328 RPs, found 8 cases without residual cancer on RP, for an incidence of 0.6%. Five of these cases were from hormonally treated patients and only 3 from untreated patients.…”
Section: Commentmentioning
confidence: 99%
“…Both cases involved low-grade and early stage disease with low-volume tumors in the biopsy specimens. The authors proposed that the possible reasons for vanishing cancer in biopsy proven specimens as early detection of prostate cancer in asymptomatic men (2,3) and a larger number of low-stage cancers being treated by prostatectomy. In early stage and low volume tumors (<0.01 cc), determining the residual microscopic tumor in the radical prostatectomy specimen is challenging for the pathologist.…”
Section: Introductionmentioning
confidence: 99%